A Pedagogical Model for Worship Literacy: Integrating the Skill Mastery Pyramid in Islamic Religious Education - Ferianto Ferianto; Agus Susanto; Muhammatkasibudi Hajimasamae (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Worship literacy among madrasah students still shows a gap between conceptual understanding and practical skills due to pedagogical strategies that are not yet systematic and tiered. This condition emphasizes the need for a learning model that is able to integrate cognitive, affective, and psychomotor dimensions gradually in Islamic Religious Education. This study discusses the integration of the Skill Mastery Pyramid Approach in Islamic Religious Education learning to improve the worship literacy of students at Madrasah Insan Kamil Karawang. This learning model is structured hierarchically through four main stages: mastery of basic knowledge, understanding of rules, application of skills, and internalization of worship values. This study uses a qualitative approach with a case study design, involving three Islamic Education teachers and twenty students during three months of observation. Data were collected through in-depth interviews, observations, and analysis of madrasah curriculum documents, with validity reinforced through triangulation of sources and time. Data analysis was conducted thematically to find patterns of improvement in worship literacy. The results showed that the application of the Skill Mastery Pyramid contributed to an increase in students' conceptual understanding, practical skills, and spiritual awareness in performing worship. Each stage of the pyramid strengthens the accuracy of worship, reinforces faith, and shapes Islamic morals. These findings indicate that the Skill Mastery Pyramid Approach is effective as an innovative strategy in competency-based Islamic Religious Education learning.